2015
DOI: 10.1097/shk.0000000000000444
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Muscle Loss is Associated with TNF Mediated Insufficient Skeletal Myogenic Activation After Burn

Abstract: Muscle loss accompanies severe burn; in this hyper-catabolic state, muscle undergoes atrophy through protein degradation and disuse. Muscle volume is related to the relative rates of cellular degradation and myogenesis. We hypothesize that muscle atrophy after injury is in part due to insufficient myogenesis associated with the hyper-inflammatory response. The aim of the study is to investigate the role of skeletal myogenesis and muscle cell homeostasis in response to severe burn. Twenty-eight male C57BL6 mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
36
3

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 35 publications
11
36
3
Order By: Relevance
“…Burn injury-induced myounclear turnover and myofiber regeneration require adequate and appropriate satellite cell activity and suggest a critical role for satellite cells in skeletal muscle atrophy and recovery following burn trauma. Similar findings reported by Song et al show activation of satellite cells alongside myonuclear apoptosis in mouse muscle following a scald burn (19**). However, the observed myogenesis post-scald likely does not counterbalance the increased cell death after burn, contributing to burn-induced cachexia (19**).…”
Section: Satellite Cell Alterations During Chronic and Acute Illnesssupporting
confidence: 87%
See 2 more Smart Citations
“…Burn injury-induced myounclear turnover and myofiber regeneration require adequate and appropriate satellite cell activity and suggest a critical role for satellite cells in skeletal muscle atrophy and recovery following burn trauma. Similar findings reported by Song et al show activation of satellite cells alongside myonuclear apoptosis in mouse muscle following a scald burn (19**). However, the observed myogenesis post-scald likely does not counterbalance the increased cell death after burn, contributing to burn-induced cachexia (19**).…”
Section: Satellite Cell Alterations During Chronic and Acute Illnesssupporting
confidence: 87%
“…Similar findings reported by Song et al show activation of satellite cells alongside myonuclear apoptosis in mouse muscle following a scald burn (19**). However, the observed myogenesis post-scald likely does not counterbalance the increased cell death after burn, contributing to burn-induced cachexia (19**). Additionally, inflammation through tumor necrosis factor-α may attenuate the myogenic response to a thermal injury, mitigating the recovery of atrophied muscle (19**).…”
Section: Satellite Cell Alterations During Chronic and Acute Illnesssupporting
confidence: 87%
See 1 more Smart Citation
“…We previously observed that TNF plays a role in insufficient myogenic activation, contributing to muscle mass loss after burn (33). A recent study from Ueki’s report showed elevated fibrinogen levels in plasma-related muscle wasting in burn mice.…”
Section: Discussionmentioning
confidence: 99%
“…TNF‐α increases in the serum of men during aging (Léger, Derave, Bock, Hespel, & Russell, 2008) which correlates with the loss of muscle mass and strength (Greiwe, Cheng, Rubin, Yarasheski, & Semenkovich, 2001; Visser et al, 2002). Moreover, in other models of muscle atrophy that include cachexia and injury‐induced muscle atrophy, administration of exogenous TNF‐α to mice decreases muscle mass and regenerative capacity (Coletti, Moresi, Adamo, Molinaro, & Sassoon, 2005; Song, Saeman, Libero, & Wolf, 2015). Those data suggest that macrophage‐secreted TNF‐α may play an important role in muscle aging.…”
Section: Introductionmentioning
confidence: 99%